The British big society effect: the challenges of the third sector. (2015) - Halsall, Jamie P.; Cook, Ian G.; Wankhade, Paresh
The voluntary sector, or the 'third sector', as it is frequently known in social policy circles has been at the centre of social action in the UK for many years. When the New Labour Government came into power back in 1997 the third sector had become more visible and the government of the day had great expectations of the positive impact that the third sector promised. Since this time there has been a belief in central government that the third sector plays a vital role in enhancing civil society and of strengthening the functionality of local communities. In May 2010, the coalition government implemented the concept of the big society. Overall the big society is recognised as a pivotal player in the relationship between citizens and the state. The third sector is perceived as a principle mechanism for implementing the big society vision. This paper aims to critically explore the big society's impact on the third sector, within the context of the current global economic recession.